Media Agenda Building Of The Malaysiakini And Agendadaily Web Sites’ During The Campaign Period Of 2004 General Election - Shaik, Abdul Rahman (2009)

(untitled)
The study was conducted to identify the main issue of the themes and to examine the patterns flow of the salient issues in the online news coverage. The study also examined the reporting attribute of Malaysiakini and Agendadaily web sites during period 2004 general election campaign. The theory that under pin this study is the media agenda building priming process derived from the Agenda Setting Theory. 184 political news articles of Malaysiakini and Agendadaily websites were analyzed using both qualitative and quantitative approaches. The findings showed that there were five main issue themes that frequently emerged in both web sites. The major themes are internal dispute, propaganda, candidate credibility, Election Commission credibility, and misconduct. The main issue themes can be categorized either into political issue and general election progress. The study on the patterns flow of the salient issues indicated the existence of media priming agenda building in the political news coverage of both web sites during the 2004 general election campaign and thus, strengthened the Agenda Setting Theory. The findings clearly indicate that the reporting attribute of the news coverage of Malaysia and Agendadaily leans towards political parties that contested in the elections. Hence, the scenario contradicted the main mission of both web sites which emphasized their news coverage were independent and fair.